Consuming Passions: Sidney Sheldon, the ’Female Gothic’ of the 1980s, and the Psychology of the Woman Reader - Mukhammadjonova, Aziza (The Lingua Spectrum, 2025)
This article explores Sidney Sheldon’s contribution to the revival of the “Female Gothic” tradition in the 1980s through complex psychological dimensions in his female characters and their cultural resonance among women readers. Though Sheldon’s works have oftentimes been relegated to the status of popular entertainment or mass-market fiction, this research will argue that his narratives actually contain deep insights into women’s experiences of power, fear, and self-realization. By using a feminist literary perspective combined with qualitative textual analysis, this study explores how Sheldon reinterprets classical Gothic conventions – such as entrapment, secrecy, and moral tension – within a contemporary social framework which reflects late twentieth-century gender anxieties. This article explores how the female protagonists of Sheldon’s novels interact with hostile or manipulative environments and are transformed from potential victim to agent. Sheldon’s blend of suspense, romance, and psychological conflict not only gave new life to Gothic tropes but also allowed for an expression of women’s pent-up emotions and ambitions. The research discusses the psychological appeal of Sheldon’s fiction in such a way that his portrayal of intelligent, resilient women resisting patriarchal strictness offers a form of emotional catharsis and empowerment for his preponderantly female readership.